Impairments Compensation in 5G PAs Using Neural Networks - Al Najjar, Reem (2024)
A Master of Science thesis in Electrical Engineering by Reem Al Najjar entitled, “Impairments Compensation in 5G PAs Using Neural Networks”, submitted in May 2024. Thesis advisor is Dr. Oualid Hammi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).